Simulation of Prostate Specific Antigen (PSA) ISFET Sensor with Different Nanostructures - Mun, Lee Shung; Mohamed Sultan, Suhana; Ab Razak, Nur Afiqah (ELEKTRIKA- Journal of Electrical Engineering, 2023)
It is crucial to have early detection of prostate cancer as it is the third most common cancer in men and Prostate Specific Antigen (PSA) is a protein-based biomarker commonly used to achieve the purpose. Besides, ISFET integrated with nanostructures such as nanowire and nanosphere has been the focus of research for disease diagnosis. Simulations are carried out in Biosensor Lab to investigate the performance of ISFET with planar, nanowire and nanosphere structures in detecting PSA. Using nanostructured ISFET in disease diagnosis is demonstrated by comparing the performance with the surface-to-volume (S/V) ratio. The nanosphere biosensor with the highest S/V ratio showed the lowest settling time when there was a low analyte concentration. Its settling time is 788 times lower than planar and almost 3 times lower than nanowire ISFET. In addition, the time needed for a planar biosensor to capture M of PSA is 5 times slower than a nanowire biosensor and nanosphere biosensor. In signal-to-noise ratio (SNR), nanosphere ISFET exhibits the highest value compared to other structures. These results indicate that a higher S/V ratio contributed to better performance in detecting PSA.